2021
DOI: 10.3389/fcvm.2021.730298
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Dynamics Required for the Degradation and Restoration of the Vascular Endothelial Glycocalyx Layer in Lipopolysaccharide-Treated Septic Mice

Abstract: The endothelial glycocalyx (GCX) plays a key role in the development of organ failure following sepsis. Researchers have investigated GCX degradation caused by pathological conditions. Nonetheless, the GCX restoration process remains poorly understood. Herein, we developed a model in which GCX restoration could be reproduced in mice using in vivo imaging and a dorsal skinfold chamber (DSC). The severity of sepsis was controlled by adjusting the dose of lipopolysaccharide (LPS) used to trigger GCX degradation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Data show that recovery of the hemodynamically significant glycocalyx layer may take up to several days after various lesions [ 38 ]. However, under specific conditions, endothelial cells appear to have the potential to regenerate the glycocalyx entirely within 24 h from violation [ 38 , 39 ]. One research showed glycocalyx recovery during experimental hemorrhagic shock in rats within 1 h after administration of 15 mL/kg of fresh-frozen plasma [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data show that recovery of the hemodynamically significant glycocalyx layer may take up to several days after various lesions [ 38 ]. However, under specific conditions, endothelial cells appear to have the potential to regenerate the glycocalyx entirely within 24 h from violation [ 38 , 39 ]. One research showed glycocalyx recovery during experimental hemorrhagic shock in rats within 1 h after administration of 15 mL/kg of fresh-frozen plasma [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on animals suggests that the endothelium glycocalyx takes five to seven days to restore after shedding [90]. However, clinical investigations have shown that this process occurs much faster [58,91].…”
Section: Emerging Insights Into the Endothelial Glycocalyx During Hea...mentioning
confidence: 99%